Development of a sandwich format, amperometric screen-printed uric acid biosensor for urine analysis - Kanyong, P.; Pemberton, R.M.; Jackson, S.K.; Hart, J.P. (Analytical biochemistry, 2012)
A screen-printed carbon electrode (SPCE) incorporating the electrocatalyst cobalt phthalocyanine (CoPC), fabricated using a water-based ink formulation, has been investigated as the base transducer for a uric acid biosensor. A sandwich biosensor was fabricated by first depositing cellulose acetate (CA) onto this transducer (CoPC–SPCE), followed by uricase (UOX) and finally a polycarbonate (PC) membrane; this device is designated PC–UOX–CA–CoPC–SPCE. This biosensor was used in conjunction with chronoamperometry to optimize the conditions for the analysis of urine: temperature, 35°C; buffer, pH 9.2; ionic strength, 50mM; uricase, 0.6U; incubation time, 180s. The proposed biosensor was applied to urine from a healthy subject. The precision determined on unspiked urine (n=6) was 5.82%. Urine was fortified with 0.225mM UA, and the resulting precision and recovery were 4.21 and 97.3%, respectively. The linear working range of the biosensor was found to be 0.015 to 0.25mM (the former represents the detection limit), and the sensitivity was calculated to be 2.10μA/mM.